Immunomodulatory Effect of Momordica charantia L. Fruit Ethanol Extract on Phagocytic Activity and Capacity of Mice Peritoneal Macrophages - Parawansah Parawansah; Tomy Nurtamin; Sufiah Asri Mulyawati; Nuralifah Nuralifah; Wa Ode Arlina Misnaeni (The Indonesian Biomedical Journal, 2018)
BACKGROUND: The purpose of this research is to understand the secondary metabolites of Momordica charantia L. extract, as well as to disclose the potential of M. charantia extract in the phagocytic activity and capacity of peritoneummacrophages.METHODS: Examination of immunomodulatory effect was done by giving M. charantia ethanol extract on 5 treatment groups, given intra-peritoneally to mice daily. Echinacea extract as positive control and double distilled water as negative control were also given. On the 8th day, mice were infected with Staphylococcus epidermidis. After 30 minutes, peritoneum fluid was obtained to observe the activity and capacity of macrophage cells.RESULTS: The results showed significant phagocytic activity (p<0.05) at a concentration of 1,200 ppm compare to the other groups. Meanwhile the macrophage cell capacity was found statistically insignificant (p>0.05). The highest phagocytic activity was the group treated with 1,200 ppm (62%), significantly higher than other groups.CONCLUSION: The secondary metabolite content of M. charantia is alkaloids, flavonoids, tannins, saponins, and triterpenoids. The 1,200 ppm M. charantia ethanol extract is potential in inducing phagocytic activity and capacity. These results indicate that the M. charantia can be suggested as a natural immunomodulator.KEYWORDS: pare fruit, Momordica charantia L., phagocytosis, macrophage, immunomodulator